Pathology and bronchoscopic studies in Mycoplasma mycoides subsp. capri infection in goats - KUMAR, HARENDRA; PARIHAR, N S; KALICHARAN, KALICHARAN; SINGH, K P (The Indian Journal of Animal Sciences, 2013)
Pleuropneumonic symptoms and lesions were produced in goals experimentally infected with bronchoscopic inoculations of Mycoplasma mycoides subsp. capri. Hyperthermia (104o-106oF) and respiratory distress with coarse moist fales, besides dullness, depression and coughing resulted due toinfection. Bronchoalvcolar lavage cytology revealed mild neutrophilia (58%),lymphoeytopenia (20%) and mild monocytosis (17%) indicating strong correlation with haematological findings. Haemograms were depressed. Pathoanatomically the apical and intermediate 1000s were the most frequently affected. The pleura and interlobular septa were oedematous, variously thickened with fibrinous exudate and infiltrated with neutrophils and mononuclear cells. The alveoli and bronchioles were usually filled with denseaggregates of neutrophils and macrophages. Mediastinal and bronchial lymphnodes revealed neutrophilic infiltration in subcapsular and medullary sinuses, besides congestion. Other visceral organs reveuled vascular congestion.